The prevalence and complications of preeclampsia in Benue South, Nigeria - Ujah, Otobo Innocent; Ochejele, Silas; Onoja, Michael Anthony; Irowa, Omoregie; Ogwuche, Paul Ejeh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Preeclampsia (PE) is the second leading cause of maternal morbidity and mortality in Sub-Saharan Africa. There is a lack of research describing the burden of preeclampsia and its associated morbidities in Benue South, Nigeria. This study aims to determine the prevalence, risk factors, and complications of preeclampsia among antenatal patients in Benue South, Nigeria. Methods: This health facility-based descriptive cross-sectional study was conducted among 238 antenatal patients in three general hospitals and one mission hospital across four local government areas in Benue South. Ethical approval was obtained from the Ethical Committee of the Federal University of Health Sciences, Otukpo. Data were collected from patients’ medical records and interviews using a pretested, structured online questionnaire via Kobo Collect. Data were uploaded into an excel spreadsheet, cleaned and analysis was performed using SPSS version 20. Results: A total of 238 pregnant women participated in the study from the Benue South senatorial zone, of which 45 had preeclampsia, giving a prevalence rate of 18.9%. Headache (84.4%) was the most common complication associated with preeclampsia. No factors were found to be significantly associated with preeclampsia in the multiple regression analysis. Conclusions: This study highlights the high prevalence of preeclampsia in Benue South. There is a need to train health workers on the prevention, identification, and management of preeclampsia to reduce the complications associated with the disease.